THE SUBSISTENCE AND SEMI-SUBSISTENCE FARMS IN ROMANIAN AGRICULTURE - Diaconu, Amelia (Economics of Agriculture, 2012)
For the integration process, agriculture is considered a sensible sector due to its importance for candidate countries and due to its agrarian potential that these countries bring along the already existing one in the European Union. The performance in agriculture has decreased and has become more and more instable. This is the result of a dual and "old" structure of the agrarian exploitations, the lack of markets that could support the restructuring and modernization of the agrarian sector and of the alimentary industry that has not yet closed the cycle of restructuring and modernization.